2022
DOI: 10.1007/s40797-022-00196-1
|View full text |Cite
|
Sign up to set email alerts
|

Investment Subsidies Effectiveness: Evidence from a Regional Program

Abstract: I provide novel empirical evidence on the effectiveness of public funding in lagging behind areas by investigating the effect of a subsidy program implemented in the Campania region (South Italy) and targeting SMEs. By relying on a Difference-in-Differences approach, my estimates demonstrate that the regional program produces a sizable increase in private firms’ innovative investment spending. However, I show also large heterogeneity in the firms’ response. In particular, I find that the positive effect on inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Using propensity score matching, they found that collaborative R&D subsidies increased later networking while individual R&D subsidies increased unsubsidized R&D spending. Chinetti [8] analyzed investment subsidies for innovation in Italian lagging regions, finding a positive effect on treated firms' investment spending using a differencein-differences approach.…”
Section: Introductionmentioning
confidence: 99%
“…Using propensity score matching, they found that collaborative R&D subsidies increased later networking while individual R&D subsidies increased unsubsidized R&D spending. Chinetti [8] analyzed investment subsidies for innovation in Italian lagging regions, finding a positive effect on treated firms' investment spending using a differencein-differences approach.…”
Section: Introductionmentioning
confidence: 99%